Unlocking Prosperity: The Role of ICTs in Alleviating Poverty in Middle East and Africa - ElNemr, Yousra (AUC Knowledge Fountain, 2024)
Most countries in the Middle East and Africa region (MEA) have recently witnessed digital improvements despite the increase in poverty rates. This thesis investigates the potential relationship of Information and Communication Technologies and poverty reduction using annual unbalanced panel data for 21 MENA countries and 48 Sub Saharan African (SSA) countries from 1990 to 2022. By focusing on two primary ICT indicators representing ICT usage and access—internet penetration and mobile subscriptions— our research applies Fixed-Effects Two Stage Least Square (2SLS) economic model to explore their relationship with the poverty headcount ratio at the $2.15 per day international poverty line. The 2SLS results suggest a significant, negative correlation between ICT and the poverty headcount ratio in MEA countries. In other words, an improvement in both the internet access and the mobile usage is associated with a significant decrease in the poverty headcount ratio, controlling for other variables. These results are robust to different estimation techniques.